Sensitivity of Debt Flows to Fiscal External Shocks in Emerging Market and Capital Market Correlations - Özker, Ahmet Niyazi (Advances in Social Sciences Research Journal, 2021)
In this study, we attempted to reveal the reasons for possible debt changes regarding the sensitivity of capital change indices in emerging economies to global financial risks and the meaning of possible correlation effects at the global level. Overcoming to Global economic and financial instabilities in emerging economies have required to take different fiscal measure have been aimed at balancing the rising interest rates and global financial change costs, which are caused by rising global priority costs. The external effects of global financial shocks in emerging economies led to a significant increase in global borrowing in these economies. In other words, in these countries representing emerging economies at different levels of development, they have also provided a reason for the inclusion of different financial and monetary policies in the process. Sensitivity to global financial shocks in emerging economies is related to the structural characteristics of countries and structural impact scales and correlations regarding which markets are affected by the needs. In this respect, it appears that the developments regarding the sectors, especially the capital flow, are meaningful in terms of indexes created by the periodic changes in the values of the current change. In this respect, in emerging economies, these shocks mostly emerge with effects giving different correlation results in countries that differ according to global crises and have other capital accumulations. The remarkable point in terms of the correlations determined here is that debt ratios and capital accumulation variations in emerging economies have put forth a significant correlation in a period of global financial shocks.